2022
DOI: 10.1002/advs.202202393
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Immune Signals to Program Innate Immunity through Rational Adjuvant Design

Abstract: Recent clinical studies show activating multiple innate immune pathways drives robust responses in infection and cancer. Biomaterials offer useful features to deliver multiple cargos, but add translational complexity and intrinsic immune signatures that complicate rational design. Here a modular adjuvant platform is created using self-assembly to build nanostructured capsules comprised entirely of antigens and multiple classes of toll-like receptor agonists (TLRas). These assemblies sequester TLR to endolysoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…[ 154 ] This highlights another advantage of model antigen delivery with MNAs: the in vivo effect of adjuvant delivery to APCs can be isolated, contributing to rational design approaches for vaccine adjuvants. [ 155,156 ] Knowledge gained from these studies can be applied to other types of disease models.…”
Section: Mnas Are Being Explored To Treat Infectious Cancerous Allerg...mentioning
confidence: 99%
“…[ 154 ] This highlights another advantage of model antigen delivery with MNAs: the in vivo effect of adjuvant delivery to APCs can be isolated, contributing to rational design approaches for vaccine adjuvants. [ 155,156 ] Knowledge gained from these studies can be applied to other types of disease models.…”
Section: Mnas Are Being Explored To Treat Infectious Cancerous Allerg...mentioning
confidence: 99%
“…These studies showed that the ratio of included TLRas dictated levels of corresponding TLR activation and levels of tumor protection in a mouse melanoma model. Interestingly, in a prophylactic vaccine regimen, a vaccine of iPEMs containing a 1:1 ratio of TLR3a:TLR9a with antigen protected mice better than soluble signals or iPEMs containing a single TLRa and antigen (Figure J,K) …”
Section: Self-assembled Materials To Probe and Regulate Immune Responsesmentioning
confidence: 99%
“…Interestingly, in a prophylactic vaccine regimen, a vaccine of iPEMs containing a 1:1 ratio of TLR3a:TLR9a with antigen protected mice better than soluble signals or iPEMs containing a single TLRa and antigen (Figure 3J,K). 35…”
Section: Self-assembled Materials To Probe and Regulate Immune Responsesmentioning
confidence: 99%
“…[165][166][167] SNAs can incorporate PRR agonists or antagonists for receptor-mediated targeting to bias the innate immune response towards specific phenotypes. 168 SNAs are composed of oligonucleotides arranged radially around a nanoparticle core; they are preferentially taken up compared to free linear oligonucleotides in over 60 cell types due to their multivalent interactions with scavenger receptors on the cell surface resulting in caveolaemediated endocytosis. 169 Hybridized DNA structures (i.e., polypods) that present DNA have also been utilized to increase uptake.…”
Section: Uptake and Targetingmentioning
confidence: 99%